2009
DOI: 10.1007/s11255-009-9525-1
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin and endogenous secretory receptor for advanced glycation end-products in diabetic type 2 and non-diabetic patients undergoing intermittent hemodialysis

Abstract: Serum concentrations of visfatin and esRAGE are increased in IHD patients. There is no difference in visfatin and esRAGE levels between diabetic and non-diabetic IHD patients. In diabetic IHD patients receiving insulin, lower esRAGE levels are associated with higher insulin resistance, whereas plasma visfatin level is positively related to plasma insulin concentration. Waist-to-height ratio is a significant determinant of plasma visfatin level and HOMA-IR. Insulin resistance seems to be a link between esRAGE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…Visfatin levels did not differ between diabetics and non-diabetics HD patients and consequently the existence of diabetics in the HD patients group did not contribute to the elevated visfatin levels. This is in accordance with previous studies performed in diabetics and non-diabetics HD patients 9,10 but in discrepancy with the general population in which visfatin is increased in type II diabetic patients. 18 Visfatin is also increased in case of obesity and metabolic syndrome.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Visfatin levels did not differ between diabetics and non-diabetics HD patients and consequently the existence of diabetics in the HD patients group did not contribute to the elevated visfatin levels. This is in accordance with previous studies performed in diabetics and non-diabetics HD patients 9,10 but in discrepancy with the general population in which visfatin is increased in type II diabetic patients. 18 Visfatin is also increased in case of obesity and metabolic syndrome.…”
Section: Discussionsupporting
confidence: 90%
“…6,7 Several studies have shown elevated serum visfatin level in HD and/or associations with metabolic parameters, atherosclerosis, and inflammation. [8][9][10][11][12][13] In patients with insulin resistance, iron metabolism is disturbed.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, it was shown that plasma visfatin/NAMPT levels are higher in subjects diagnosed with type 2 diabetes 42 and are increased by both endo-and exogenous insulin. 43 In addition, elevated visfatin/NAMPT levels were associated with progressive beta-cell dysfunction. 44 It was suggested that increased circulating visfatin/ NAMPT level is a counter-regulatory mechanism for insulin resistance and insulin deficiency.…”
Section: Discussionmentioning
confidence: 99%